Self E-Commerce Platform Advertisement In Encouraging Transaction Development Of Indonesian Creative Products - Randika Fandiyanto, Raden Andi Sularso, Bambang Irawan, Ika Barokah Suryaningsih (International Journal of Advanced Science and Technology, 2020)
This research was conducted to prove the SEPAd variable, which moderates the trust of its influence on purchasing decisions and online repurchase interests. This research was conducted on consumers of creative products in e-commerce in Indonesia. The number of samples is 185 respondents purposively. Analysis of the data used is Structural Equation Modeling (SEM). The findings show that Perceived Risk has a significant negative effect on E-Trust, while Perceived Ease of Use and Perceived Usefulness has no significant effect on E-trust. While Perceived Risk, Perceived Ease of Use, and Perceived Usefulness do not have a significant effect on Purchase Decision. The indirect effect through the intervening variable E-trust on Purchase Decision is more significant. SEPAd significantly weakens the effect of Perceived Risk on E-trusts and strengthens the effect of Perceived Usefulness on E-Trust. In contrast, the Perceived Usefulness does not significantly influence the effect. Purchase Decision has a significant effect on E-Satisfaction, and E-Satisfaction has a significant effect on Repurchase Intention. This study can then help researchers and apply to creative industry players in Indonesia.